Thoracoscopic lobectomy using indocyanine green fluorescence to detect the interlobar fissure in a patient with displaced B3 and absence of fissure: A case report. Issue 7 (19th June 2019) - Nakanishi, Keita; Kuroda, Hiroaki; Nakada, Takeo; Ueno, Harushi; Sakakura, Noriaki
Abstract : A 90‐year‐old woman was admitted to our hospital with suspected lung adenocarcinoma. Preoperative three‐dimensional reconstructed computed tomography revealed displacement of the anterior segmental bronchus (B3) arising from the right middle lobe bronchus with absence of the fissure between the right upper and middle lobes. A complete thoracoscopic right upper lobectomy was successfully performed. It is crucial to identify such anomalies prior to lung resection to avoid intraoperative complications during thoracoscopic lobectomy or segmentectomy. Additionally, intravenous indocyanine green with a fluorescence system was useful to identify the proper interlobar fissure boundary intraoperatively. To the best of our knowledge, this is the first reported case of thoracoscopic lobectomy for lung cancer with displaced B3 and absence of the interlobar fissure to be performed by applying the intravenous indocyanine green method.